Extracorporeal Treatment for Methotrexate Poisoning: Systematic Review and Recommendations from the EXTRIP Workgroup. Issue 4 (April 2022) - Ghannoum, Marc; Roberts, Darren M.; Goldfarb, David S.; Heldrup, Jesper; Anseeuw, Kurt; Galvao, Tais F.; Nolin, Thomas D.; Hoffman, Robert S.; Lavergne, Valery; Meyers, Paul; Gosselin, Sophie; Botnaru, Tudor; et al.
Abstract : Methotrexate is used in the treatment of many malignancies, rheumatological diseases, and inflammatory bowel disease. Toxicity from use is associated with severe morbidity and mortality. Rescue treatments include intravenous hydration, folinic acid, and, in some centers, glucarpidase. We conducted systematic reviews of the literature following published EXtracorporeal TReatments In Poisoning (EXTRIP) methods to determine the utility of extracorporeal treatments in the management of methotrexate toxicity. The quality of the evidence and the strength of recommendations (either "strong" or "weak/conditional") were graded according to the GRADE approach. A formal voting process using a modified Delphi method assessed the level of agreement between panelists on the final recommendations. A total of 92 articles met inclusion criteria. Toxicokinetic data were available on 90 patients (89 with impaired kidney function). Methotrexate was considered to be moderately dialyzable by intermittent hemodialysis. Data were available for clinical analysis on 109 patients (high-dose methotrexate [>0.5 g/m 2 ]: 91 patients; low-dose [≤0.5 g/m 2 ]: 18). Overall mortality in these publications was 19.5% and 26.7% in those with high-dose and low-dose methotrexate–related toxicity, respectively. Although one observational study reported lower mortality in patients treated with glucarpidase compared with those treated with hemodialysis, there were important limitations in the study. For patients with severe methotrexate toxicity receiving standard care, the EXTRIP workgroup: ( 1 ) suggested against extracorporeal treatments when glucarpidase is not administered; ( 2 ) recommended against extracorporeal treatments when glucarpidase is administered; and ( 3 ) recommended against extracorporeal treatments instead of administering glucarpidase. The quality of evidence for these recommendations was very low. Rationales for these recommendations included: ( 1 ) extracorporeal treatments mainly remove drugs in the intravascular compartment, whereas methotrexate rapidly distributes into cells; ( 2 ) extracorporeal treatments remove folinic acid; ( 3 ) in rare cases where fast removal of methotrexate is required, glucarpidase will outperform any extracorporeal treatment; and ( 4 ) extracorporeal treatments do not appear to reduce the incidence and magnitude of methotrexate toxicity.